2012
DOI: 10.1007/s00432-012-1187-1
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with AT-101 enhances tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis of breast cancer cells by inducing death receptors 4 and 5 protein levels

Abstract: These findings all together, strongly suggest that pretreatment with AT-101 enhances TRAIL-induced death-inducing signaling complex resulting in the engagement of the mitochondrial pathway to apoptosis in breast cancer cells. These promising, preliminary results make AT-101 and TRAIL a novel combination treatment candidate for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Similar to previously published studies [ 38 ], we observed that gossypol and ApoG2 did not affect the proliferation of normal breast epithelial cells. This observation can, in part, be explained by the negligible levels of copper present in these cells as compared to breast cancer cells [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previously published studies [ 38 ], we observed that gossypol and ApoG2 did not affect the proliferation of normal breast epithelial cells. This observation can, in part, be explained by the negligible levels of copper present in these cells as compared to breast cancer cells [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Numerous compounds have been reported to synergistically act with TRAIL to potentiate apoptosis in these cells, including chemotherapeutic drugs and natural compounds. [40][41][42][43][44][45] Our results added the usage of brequinar into this continuously growing list of agents that can be utilized in TRAIL combinatorial therapy. Interestingly, the combined treatment of brequinar and TRAIL did not harm the mammary epithelial cells HMEC suggesting normal cells possess own mechanisms to overcome the sensitization effect.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar intervertebral disc degeneration is manifested with chronic pains in waist and legs, numbness and fatigue [ 7 , 8 ]. Previous studies suggested the participation of cytokines as critical inflammatory factors in the occurrence and progression of degenerative osteoarticular disease and osteoarthritis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%